DETERMINASI PEMBERIAN SUKROSA TERHADAP KADAR SGPT DAN SGOT TIKUS GALUR WISTAR SEBAGAI INDIKATOR FUNGSI HATI: Determination of High Sucrose Intake to SGPT and SGOT Concentration in Wistar Rats As Indicator of Liver Function. - Andayani, Prawita Lintang; Santoso, Koekoeh; Kusumorini, Nastiti; Satyaningtijas, Aryani Sismin; Supiyani, Atin (Bioma, 2016)
The aim of the study was to determine the correlation between sucrose intake at various administration doses to SGPT and SGOT level in Wistar rats. SGPT and SGOT level in blood serum were used as parameter of liver function. Twelve rats were grouped according to administration doses (20%, 40%, 60% of given feed total energy and control group). Sucrose was administered orally once a day for 70 days at given doses by force feeding. SGPT dan SGOT level were measured using SGPT and SGOT Test Kit and read using spectrophotometer. The result indicated that increased administration dose caused a significant increase of SGPT and SGOT level.